Analisis Postur Kerja pada Operator Quality Control Terhadap Kualitas Kinerja Menggunakan Metode RULA di PT XYZ - Mahmuda, Muhammad Hatta; Rahma, Rana Ardila (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
In work in the current industrial era, both on a small and large scale, there is almost always a risk of danger. One of them is an occupational disease caused by errors in body posture when doing work. This research aims to analyze the body posture and performance of an employee in the quality control division. The method used is the Nordic body map questionnaire and RULA calculations. The results obtained were that the job of polishing components and measuring components got a grand score of 7. Meanwhile, the job of wiping components and checking data got a grand score of 4. So the body posture of the quality control division employees was not ergonomic and needed to be repaired.